A Portrait Head of Severus Alexander in Delft - Heijnen, Sam; Moormann, Eric M. (Archäologischer Anzeiger, 2020)
An as yet unpublished ancient marble head from the Paul Tétar collection in Delft (NL) can be interpreted as a portrait of Emperor Severus Alexander (222–235 A.D.). The provenance of the piece is unknown. On the basis of the bearded cheeks and moustache as well as other criteria the portrait must be classified in ›Group C‹ of the official portrait type of the emperor and dated to c. 225 A.D. Thus 31 portraits of the emperor are known in total.